Small Mammals from Lanjak Entimau Wildlife Sanctuary "hidden Jewel of Sarawak" - Roberta Chaya, Tawie Tingga; Mohd Ridwan, Abd Rahman; Anang Setiawan, Achmadi; Sigit, Wiantoro; Besar, Ketol; Huzal Irwan, Husin; Wahap, Marni; Mohd Jalani, Mortada; F. A., Anwarali; Mohd Tajuddin, Abdullah (Akademi Sains Malaysia, 2010)
A survey was conducted at Lanjak Entimau Wildlife Sanctuary (LEWS) from 13th to 26th June 2008 to document as well as to determine the species richness and relative abundance of small mammals. In average, 10 mist nets, six four-bank harp traps, 10 pit fall traps and 100 cage traps were deployed. Sampling was conducted at two different sites within the sanctuary: Sungai Bloh (Bloh) and Sungai Menyarin (Menyarin) trail. A total of 77 specimens from 21 species of nine families of small mammals representing four orders: Chiroptera, Rodentia, Scandentia and Soricomorpha were captured from 12 nights of sampling effort. Balionycteris maculata and Niviventer rapit were recorded as the most abundant species in both sites. Ten new geographic records were added for Hipposideros cervinus, H. cinneraceus, Rhinolophus luctus, Kerivoula hardwickii, K. intermedia, Myotis muricola, M. ridleyi, Arielulus cuprosus, Tupaia minor and Suncus etruscus at LEWS. Current study does not provide similar survey result to the previous study, which may be due to differences in sampling seasons, baits used, and the exact sampling site. We have provided detailed exact sampling sites geographic coordinate and sampling techniques to allow future sampling to replicate our survey to compare and discuss the diversity in LEWS over time.